pengaruh PENGARUH VARIASI KONSENTRASI HPMC TERHADAP SIFAT FISIK GEL HAND SANITIZER EKSTRAK DAUN PEPAYA (Carica papaya L.) - MIKHANIA CHRISTININGTYAS ERYANI (Politeknik Kesehatan Kemenkes Malang (State Health Polytechnic of Malang), 2021)
The aims of this research was to understand the effect of variations concentrations HPMC as gelling agent to the physical characteristic hand sanitizer gel of papaya leaves (Carica papaya L.). Gel was formulated with variation concentration of the HPMC 2% (F1), 2.5% (F2) , and 3% (F3) The active ingredient was papaya leaves extract. The ingredient use were HPMC as gelling agent, propilenglikol as humectant, methylparaben as preservative, oleum rosae as corigen odoris and aquadest as a solvent. The result of organoleptic test showed difference in consistency of gel but there were no difference in smell and color. Homogeneity test showed homogeneous result in all formulas. Viscosity test, pH, and spreadability were in accordance with the requrements. The statistic result used One Way Anova showed that there were a difference in pH and viscosity.